The Price of Complexity in Financial Networks - Battiston, S; Caldarelli, G; May, R; Roukny, T; Stiglitz, J (National Academy of Sciences, 2016)
Financial institutions form multi-layer networks of contracts among each other and exposures to common assets. As a result, the default probability of one institution depends on the default probability of all the other institutions in the network. Here, we show how small errors on the knowledge of the network of contracts can lead to large errors on the probability of systemic defaults. From the point of view of financial regulators, our findings show that the complexity of financial networks may decrease our ability to mitigate systemic risk and thus it may increase the social cost of financial crises.